IMPLEMENTASI MEDIA FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA SISWA KELAS I MI PSM NGAWI - elentika, Pramudya; Masruroh, Binti; Mulyani, Sri; Irbah, Ariq Nurjannah (Institut Agama Islam Ngawi, 2024)
This study aims to improve early reading skills with pictorial word cards for first grade students of MI PSM Kedungputri, Paron District, Ngawi Regency. This research is a descriptive qualitative Classroom Action Research (CAR) using a qualitative approach that is strengthened by a quantitative approach, taking the background of MI PSM Kedungputri, Paron District, Ngawi Regency. The subject of this research is the first grade students of MI PSM Kedungputri, Ngawi District, Ngawi Regency, while the object of this research is the improvement of early reading skills with picture word cards media on my favorite theme. The results showed that the picture word card media could improve the students' initial reading ability. The increase in student learning activities can be measured from the evaluation of cycles I, and II with the value of student learning activities in pre-cycle I of 54% with 2 students who are able to read, cycle I of 66% with 5 students who are able to read, and cycle II of 80% with 8 students who are able to read and have reached the KKM. Thus, this study proved that there was an increase in the application of pictorial word card media to the Beginning Reading Ability of Indonesian Students of Class I MI PSM Kedungputri, Paron District, Ngawi Regency.